2007
DOI: 10.1002/jat.1194
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of chloroquine in isolated rat hepatocytes

Abstract: Chloroquine is a synthetic quinoline being used as an antimalaria and antirheumatoid agent. Several cases of hepatotoxicity have been reported with the use of chloroquine. However, the mechanism(s) of its hepatotoxic effect is unknown. The purpose of this study was to investigate the cytotoxic mechanism of chloroquine. Cytotoxicity was studied using freshly isolated rat hepatocytes incubated in Krebs-Henseleit buffer under a flow of 95% O(2) and 5% CO(2). Chloroquine was toxic towards hepatocytes and caused ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Numerous studies have reported hepatotoxicity resulting from use of CQ 19, 20. Therefore, we decided to screen our five lead candidates for any potential hepatotoxicity in our final stage of ADMET screening (Figures 4a and 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported hepatotoxicity resulting from use of CQ 19, 20. Therefore, we decided to screen our five lead candidates for any potential hepatotoxicity in our final stage of ADMET screening (Figures 4a and 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocyte viability was assessed by plasma membrane disruption as determined using the Trypan blue uptake test (24). Cell viability was determined immediately after isolation and at scheduled time intervals following incubation.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…After treating a 1.0 mL aliquot of hepatocyte suspension (10 6 cells mL -1 ) with TCA (70 %) and boiling the supernatant with TBA (0.8 %) for 20 min, the absorbance of developed colour was measured at 532 nm in an Ultrospec2000 Ā® spectrophotometer (Pharmacia Biotech, Cambridge, England) (24).…”
Section: Determination Of Lipid Peroxidation In Hepatocytesmentioning
confidence: 99%
“…Some investigations indicated the role of reactive metabolites and oxidative stress in chloroquine-induced liver injury. [11][12][13][14] Bioactivation of amodiaquine to a quinone imine metabolite, 15 and oxidative stress have also been suggested to be involved in the development of amodiaquine-induced hepatotoxicity. 16,17 Drug-inflammation interaction is an intriguing model for investigating the mechanisms of drug-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%